ANALISIS PENGARUH BIAYA TRANSPORTASI TERHADAP LABA BERSIH: STUDI KUANTITATIF PADA PT. POS INDONESIA (PERSERO) PERIODE 2021–2023 - Cahyat Rohyana; Widia Mulyani (LAND JOURNAL, 2026)
Transportation costs are the total costs incurred by logistics or courier company during themovement process from the point of origin to the final destination. This study aims to analyzetransportation costs and net profit at PT Pos Indonesia (Persero) during the 2021-2023 period.Furthermore, this study also examines the effect of transportation costs on the company's netprofit. This study uses a quantitative approach. The population in this study is 36 monthly profitand loss financial statements. The sample in this study is 36 data through a saturated samplingtechnique. The data used is secondary data obtained from Pos Indonesia (Persero)'s monthlyprofit and loss financial statements for the 2021-2023 period. The analytical tools used in thisstudy are the Normality Test, Product Moment Correlation Test, Simple Linear Regression Test,Coefficient of Determination Test, and t-Test. This study uses the IBM SPSS (Statistical Productand Service Solution) version 27 application. The results of this study state that transportationcosts (X) decreased in 2022 and increased in 2023. Net profit (Y) increases annually. Based onthe testing conducted, this study states that transportation costs have no effect on net profit in the2021-2023 period. The t-test shows that the t-table value of 2.032 is greater than the calculated t-value of 1.129, with a significance value of 0.267.